Set up the equation so m<HCB + m<DCH = m<DCB
2x + 100 + 60 = x + 170
2x+ 160 = x +170
-x -x
x + 160 = 170
- 160 -160
x = 10
Answer:combining like terms is technically putting values that have the same variable (letter) Or numbers together to make a more simplified equation
Step-by-step explanation:
Answer: 37
Step-by-step explanation:
Answer:
128
Step-by-step explanation:
Answer:
![x^3+1](https://tex.z-dn.net/?f=x%5E3%2B1)
Step-by-step explanation:
![26(x^3+1)^2-22(x^3+1)-3=0](https://tex.z-dn.net/?f=%2026%28x%5E3%2B1%29%5E2-22%28x%5E3%2B1%29-3%3D0%20)
Comparing to
![A(u)^2+B(u)+C =0](https://tex.z-dn.net/?f=%20A%28u%29%5E2%2BB%28u%29%2BC%20%3D0%20)
Where A,B,C are constants
You should see that we need to substitute the
with u.